Implementasi Fun Learning Arabic dalam Pengenalan dan Pengembangan Kosakata Bahasa Arab di TK Al-Khairat Usia 5-6 Tahun - Musayyadah, Musayyadah; Pusparini, Dewi; Ismaiya, Nurul (Indo-MathEdu Intellectuals Journal, 2025)
Learning Arabic in early childhood often faces challenges, particularly in introducing vocabulary that is considered difficult and monotonous. Therefore, a joyful learning approach that aligns with children’s developmental characteristics is required. This study aims to describe the implementation of the Fun Learning Arabic method in introducing and developing Arabic vocabulary at TK Al-Khairat.This research employed a qualitative approach with a case study design. The research subjects consisted of one classroom teacher and children in group B. Data were collected through observation, interviews, and documentation, and analyzed thematically. The findings indicate that the implementation of Fun Learning Arabic through educational games, songs, flashcards, and simple motor activities successfully enhanced children’s engagement in learning and enriched their Arabic vocabulary. The children appeared more enthusiastic, active, and able to retain vocabulary effectively.The implication of this study highlights the importance of innovation in early childhood education, particularly for teachers in adopting methods that are consistent with children’s characteristics. Furthermore, teacher training is essential in developing fun learning strategies to ensure that Arabic language learning becomes more effective and meaningful.